Biliproteins of cyanobacteria and Rhodophyta: Homologous family of photosynthetic accessory pigments - Glazer, Alexander N. (1976)
Amino-terminal sequence determinations are reported of the subunits of biliproteins of prokaryotic unicellular and filamentous cyanobacteria and of eukaryotic unicellular red algae. The biliproteins examined, allophycocyanin, C-phycocyanin, R-phycocyanin, b-phycoerythrin, and phycoerythrocyanin, vary with respect to the chemical nature and the number and distribution of the bilin chromophores between the two dissimilar subunits. The amino-terminal sequences fall into two classes, “α-type” and “β-type”, with a high degree of homology within each class. In those biliproteins where the number of bilin chromophores on the two subunits is unequal, the subunit with the greater number of chromophores has the β-type amino-acid sequence. Extensive homology also exists between α- and β-type sequences, strongly supporting the view that these arose by gene duplication to give rise to the ancestral α- and β-type genes early in the evolution of the biliproteins. The subsequent generation of the various classes of biliproteins appears to be the result of further gene duplication of the α- and β-type genes, ultimately to give rise to families of polypeptide chains of similar sequence, but varying in the number of chromophore attachment sites and the structure of the chromophores.